Milwaukee's Community Development Block Grant: Connecting Youth Services and Economic Development - Shore, Bethany; Murphy, Kevin; Fitzgerald, Julie; Carlson, Nina (My University, 2007)
The City of Milwaukee uses federal block grant funds to contract with community organizations for youth services. The Milwaukee Budget Office asked the authors to review CDGA?s Youth Services grant process to determine the effectiveness of Youth Services grants and to explore the possibility of better linking Youth Services programming to economic development. The authors conclude that though CDGA?s Youth Services grantees provide quality programming, the agency should adjust its reporting and monitoring systems to yield better performance data to reflect these efforts, and that shifting more money toward youth job training and placement would not result in stronger economic development outcomes relative to other uses of those resources.